Analysis of the Influence of The 7P Marketing Mix on Customer Satisfaction of Bikla Coffee, Jember District - Renata Dian Kusuma Wardani; Teguh Soedarto; Mirza Andrian Syah (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2024)
The marketing mix is one of the strategies that must be developed to build the image of a business so that it can be a factor in increasing customer satisfaction. Consumer satisfaction refers to the degree to which an individual's actual state is influenced by comparing the apparent look of a product to their assumptions. Increasing customer satisfaction is a fundamental aspect of the sustainability of a business. Many industries have an impact on competition between businesses, so every business tries to make its customers feel satisfied. This research attempts to examine the effect of the marketing mix simultaneously and partially on customer satisfaction and measure the level of customer satisfaction. This research was conducted in Jember district from February 2024 to March 2024. The study used quantitative methods with a survey approach. This study's primary and secondary data sources are primary and secondary. Accidental sampling, a non-probability sampling technique, is utilized by the sampling approach. The data analysis approach used was the SEM (Structural Equation Model) and CSI (Customer Satisfaction Index), which used 68 respondents. The study findings reveal that the coefficient of determination (R square) is obtained at 0.578, or when percent, there are 57.8 percent. Variables that affect customer satisfaction. Partially, the price variable (X2), promotion (X4), process (X6), and physical evidence (X7) have a significant effect on customer satisfaction, while the product variable (X1), place (X3), people (X5) have no significant effect. In addition, the results of calculating the level of satisfaction of BIKLA coffee consumers show a CSI value of 79.86%, indicating that consumers are satisfied with the services provided.